DESIGNING INFORMATION SYSTEM FOR DATA COLLECTION OF ELDERLY PATIENT IN PUSKESMAS DUM SORONG CITY - Iriene Surya Rajagukguk; Razni Mardahatilla Paknawan (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2021)
The Public Health Center (Puskesmas) is an agency engaged in public health. Puskesma Dum is a public health service center located on Jl. Trikora No. 203 East Dum Village, Sorong Kepulauan District, Sorong City. Management of elderly patient data at Dum Puskesmas is still done manually, namely by means of bookkeeping. An important component in realizing effective information, manual data management has many weaknesses, apart from requiring a long time, its accuracy is also less acceptable. The purpose of this study was to design a web-based information system for elderly patient data collection at Puskesmas Dum, Sorong City. And to improve the quality of service and data collection of elderly patients. The method used in this thesis is the method of analyzing observation data, interviews and literature study, while the system development method uses the Rapid Application Development (RAD) method. System design using UML. The programming languages used are PHP and HTML and the software for interface design uses Balsamiq Mockups 3 and Brackets as text editors. Making a database using MySQL with the Xampp application.